Longitudinal section cell morphology of Chinese fir roots and the relationship between root structure and function - Li, Linxin; Zhang, Ting; Lin, Jingquan; Lian, Xiaoqian; Zou, Xianhua; Ma, Xiangqing; Wu, Pengfei (Frontiers in Ecology and Evolution, 2023)
The longitudinal section cell morphology of Chinese fir roots was studied to better understand the relationship between root structure and root function. In this study, the adjusted microwave paraffin section method and the selected two sample transparency methods were used to process the Chinese fir roots and combined with the laser scanning confocal microscopy (LSCM) technique, the morphology of Chinese fir roots longitudinal section can be clearly observed in a short time. At the same time, the observation effect of the longitudinal section cell morphology of the LSCM image of the thick section of the Chinese fir roots and the ordinary optical imaging of the thin section was analyzed and compared. The results showed that: (1) There were apparent differences in the observation effect of cell morphology in longitudinal sections of Chinese fir roots obtained using various treatment methods. Under LSCM, the section with a thickness of 20 μm generated by the microwave paraffin section technique displayed complete cell morphology and clear structure in the root cap, meristem zone, and elongation zone. The overall imaging effect was good; the thickness was 0.42-1.01, 0.64-1.57 and 0.95-2.71 mm, respectively. The cell arrangement in maturation zone cells was more regular. (2) Compared to the ordinary optical imaging of thin sections, the thick sections of roots made by the microwave paraffin section method shortened the time to obtain high-quality sections to ensure the observation effect. Therefore, adopting the microwave paraffin cutting approach to produce thicker root sections under LSCM allows for rapid observation of the cell morphology in longitudinal sections of Chinese fir roots. The current study provides the efficient operation procedure for the microscopic observation technology of the longitudinal section of Chinese fir roots, which is not only beneficial to reveal the relationship between the root structure and function from the microscopic point of view but also provides a technical reference for the anatomical study of other organs and the observation of the longitudinal section cell morphology of plant roots with similar structural characteristics.